Description of two new species of the genus Baburia Koçak, 1981 (Lepidoptera: Tortricidae: Olethreutinae) from India - Naik, Santhosh; Shashank, P. R. (Zootaxa, 2022)
The genus Baburia Koçak, 1981 of the tribe Olethreutini is newly recorded from India. Two new species B. tinsukiaensis Shashank, n. sp., and B. chettalliensis Shashank and Santhosh, n. sp. are described. This increases the number of species of Baburia to five. Photographic illustrations after the description of two new taxa, checklist and key to species of this genus are provided.